2021
DOI: 10.1088/2633-1357/abdbbb
|View full text |Cite
|
Sign up to set email alerts
|

A novel dataset for analysing sub-national socioeconomic developments in the Indian coal industry

Abstract: Coal use needs to rapidly decline in the global energy mix in the next few decades in order to meet the Paris climate goals of keeping global warming well below 2-degrees Celsius. In emerging economies such as India (the second largest producer and consumer of coal) this would entail reducing long-term coal dependency. Prior work has focused on a coal transition in India from a techno-economic point of view, yet little attention has been given to the socio-economic dimensions of this transition. This is in par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Coal accounts for approximately 55% of the total energy demand in India. It is a labourintensive sector, directly employing a workforce of 1.2 million (Pai and Zerriffi, 2021). This study also estimated that there were 744,984 direct coal mining jobs in the financial year 2019-20; moreover, it has been observed that employment in coal mines varies across districts, with Dhanbad district in Jharkhand accounting for the highest number of coal mining jobs.…”
Section: Coalmentioning
confidence: 76%
“…Coal accounts for approximately 55% of the total energy demand in India. It is a labourintensive sector, directly employing a workforce of 1.2 million (Pai and Zerriffi, 2021). This study also estimated that there were 744,984 direct coal mining jobs in the financial year 2019-20; moreover, it has been observed that employment in coal mines varies across districts, with Dhanbad district in Jharkhand accounting for the highest number of coal mining jobs.…”
Section: Coalmentioning
confidence: 76%
“…Existing renewable energy capacity is not enough to cover increased demand, as demonstrated by the situation with numerous blackouts in 2021-2022 in the face of rolling heatwaves and a shortage of thermal coal. In addition, the coal mining sector accounts for about 1.3 per cent of GDP [World Bank, n.d.], and also provides employment to more than 700 thousand people, and an even larger number of jobs indirectly related to the coal industry [Pai, Zerriffi, 2021].…”
Section: Just Energy Transition Partnershipmentioning
confidence: 99%
“…Our analysis shows that policies that have modest or negligible emissions impacts at the aggregate, national level nonetheless have disparate, state-level, spatial emissions and cost effects. Consequently, the differences that we quantify have implications for India’s decarbonization efforts as it aims to increase renewable energy by 2030 and meet net-zero emissions by 2070 while ensuring a just energy transition for coal-dependent states in eastern India ( 80 , 84 ).…”
Section: Key Findings and Policy Considerationsmentioning
confidence: 99%